Analysis of Structural Genomic Diversity in Aegilops umbellulata, Ae. markgrafii, Ae. comosa, and Ae. uniaristata by Fluorescence In Situ Hybridization Karyotyping - Song, Zhongping; Dai, Shoufen; Bao, Tingyu; Zuo, Yuanyuan; Xiang, Qin; Li, Jian; Liu, Gang; Yan, Zehong (Frontiers in Plant Science, 2020)
FISH karyotypes have been widely used for evolutionary analysis on chromosome organization and genetic/genomic diversity in the wheat alliance (tribe Triticeae of Poaceae). The karyotpic diversity of Aegilops umbellulata, Ae. markgrafii, Ae. comosa subsp. comosa and subsp. subventricosa, and Ae. uniaristata was evaluated by the fluorescence in situ hybridization (FISH) probes oligo-pSc119.2 and pTa71 in combination with (AAC)5, (ACT)7, and (CTT)12, respectively. Abundant intra- and interspecific genetic variation was discovered in Ae. umbellulata, Ae. markgrafii, and Ae. comosa, but not Ae. uniaristata. Chromosome 7 of Ae. umbellulata had more variants (six variants) than the other six U chromosomes (2–3 variants) as revealed by probes oligo-pSc119.2 and (AAC)5. Intraspecific variation in Ae. markgrafii and Ae. comosa was revealed by oligo-pSc119.2 in combination with (ACT)7 and (CTT)12, respectively. At least five variants were found in every chromosome of Ae. markgrafii and Ae. comosa, and up to 18, 10, and 15 variants were identified for chromosomes 2 of Ae. markgrafii, 4 of Ae. comosa subsp. comosa, and 6 of Ae. comosa subsp. subventricosa. The six Ae. uniaristata accessions showed identical FISH signal patterns. A large number of intra-specific polymorphic FISH signals were observed between the homologous chromosomes of Ae. markgrafii and Ae. comosa, especially chromosomes 1, 2, 4, and 7 of Ae. markgrafii, chromosome 4 of Ae. comosa subsp. comosa, and chromosome 6 of Ae. comosa subsp. subventricosa. Twelve Ae. comosa and 25 Ae. markgrafii accessions showed heteromorphism between homologous chromosomes. Additionally, a translocation between the short arms of chromosomes 1 and 7 of Ae. comosa PI 551038 was identified. The FISH karyotypes can be used to clearly identify the chromosome variations of each chromosome in these Aegilops species and also provide valuable information for understanding the evolutionary relationships and structural genomic variation among Aegilops species.